Laporan Kasus: Obstruksi Rektum dan Uretra Akibat Fibroma Serviks pada Anjing Golden Retriever (RECTAL AND URETRA OBSTRUCTION DUE TO FIBROMA CERVICES IN GOLDEN RETRIEVER DOG: CASE REPORT ) - Suartha, I Nyoman; Wirata, I Wayan; Gorda, I Wayan; Tobing, Agatha Serena Lumban; Supartika, I Ketut Eli (Jurnal Veteriner; Vol 21 No 1 (2020), 2020)
Rectal obstruction in dogs is generally caused by foreign objects such as bone or hard feces, whereas urethral obstruction is generally caused by calculi. Cases of rectal and urethral obstruction due to tumors or neoplasia in the female reproductive tract of dogs are rare. Fibroma is one type of benign tumor that attacks fibroblast tissue. The formation of the tumor results in obstruction of the gastrointestinal tract and urine. This paper aims to raise cases of rectum obstruction and vesica urinaria in dogs. Fourth yearold female golden retriever dogs was admitted to Veterinary Hospital Faculty of Veterinary Medicine Udayana University. According to the case history of owner, the dog was suffered weakness, anoreksia, bally and tend. The dog was difficult to urinate and poo. The stool was suppressed like “ornament cake birth day”. All of health condition were normal. Clinical examination revealed presence mass like tumor attached to the cervix with consistence hard and irregular form. Ultrasonography examination was distended bladder without calculi form. Hematological routine have leucophilia, anemia and thrombositopenia. After general anesthesia with ketamine HCl and xylazine, the mass with irregular form and hard consistence was surgical removed. Histophatological section were revealed presence of fibroma which represented by arrangement of cell that have feature tapering cell as fibroblast without mitosis. The mass was diagnosed as fibroma. It concluded that golden retriever dogs had obstruction of rectum and vesica urinaria as result of cervical fibroma tumors.